BAHAN AJAR PENGELOMPOKAN HEWAN BERDASARKAN JENIS MAKANANYA BERBASIS MULTIMEDIA DI KELAS 5 SDN MEKARMUKTI 1 - Jajang Supriatna; Widi Nurjaman; Nanda Mohammad Fierza (Universitas Negeri Surabaya, 2022)
Education in the 21st century begins to integrate skills, knowledge, skills and attitudes, as well as mastery of information and communication technology. Innovative learning models and teaching materials such as multimedia-based learning systems play a very important role in the development of children's education. In accordance with these needs, this study aims to design a learning media about animal grouping for students in elementary schools that is interactive as well as a display that can attract students so that it can increase students' enthusiasm for learning and understanding efficiently. Provide learning media about the introduction of animal groupings with animation and animal cartoon characters making it easier for children to learn natural sciences, especially the introduction of various types of animals. This study uses a multimedia development methodology. The multimedia method according to Luther & Sutopo consists of several stages, the first stage is the concept, this stage determines the learning objectives, user identification, application concepts and devices used. The second stage is design, this stage is carried out by designing pages, storyboards and navigation structures. The third stage is collecting material, this stage collects the materials needed in making the program. The fourth stage is assembly, in that stage the application begins to be made according to the design in the second stage and combines it with the materials that have been collected in the third stage. The fifth stage is testing, at this stage testing is carried out by application makers and users. The sixth stage is distribution, the last stage the application is saved to the storage media. The application of learning media for the introduction of animal grouping is made as attractive as possible by prioritizing visual uniqueness with animation and the addition of video features. The application of learning media for the introduction of animal grouping is made with materials that are in accordance with the competencies and learning materials